Electrochemical degradation of tetracycline hydrochloride in sulfate solutions on boron-doped diamond electrode: The accumulation and transformation of persulfate. (October 2022) - Li, Xiaobao; Fan, Shasha; Jin, Chunji; Gao, Mengchun; Zhao, Yangguo; Guo, Liang; Ji, Junyuan; She, Zonglian
Abstract: In this study, a novel electrifying mode (divided power-on and power-off stage) was applied in the system of BDD activate sulfate to degrade tetracycline hydrochloride (TCH). The BDD electrode could activate sulfate and H2 O to generate sulfate radicals (SO4 - ) and hydroxyl radicals ( OH) to remove TCH, and SO4 - could dimerize to form S2 O8 2− . Then, the S2 O8 2− was activated by heat and quinones to generate SO4 - for the continuous degradation of TCH during the power-off stage. In addition, the intermittent time has a significant effect on the degradation of TCH. Factors, affecting the accumulation of S2 O8 2−, were analyzed using a full factorial design, and the accumulation of S2 O8 2− could reach 16.2 mM in 120 min. The results of electron spin resonance and radical quenching test showed that SO4 -, OH, direct electron transfer (DET), and non-radical in the system could effectively degrade TCH, and SO4 - was dominated. The intermediate products of TCH were analyzed by HPLC-QTOF-MS/MS, and the TCH mainly underwent hydroxylation, demethylation and ring opening reactions to form small molecules, and finally mineralized. The results of the feasibility analysis revealed that some intermediates have high toxicity, but the system could improve the toxicity. The results of energy consumption indicated that the intermittent electrifying mode could make full use of the persulfate generated during the power-on stage and reduce about 30% energy consumption. In conclusion, this work demonstrated that it was economically feasible to degrade TCH in wastewater by activating sulfate with BDD electrodes with an intermittent electrifying mode. Graphical abstract: The intermittent electrifying mode proposed for the first time was applied to degrade tetracycline using a BDD electrode to activate sulfate. The degradation mechanism of TCH, the amount of persulfate accumulation and the energy consumption of this system were comprehensively evaluated, aiming to guide the industrial-scale application. Image 1 Highlights: A novel electrochemical operation mode was proposed for the degradation of TCH. Reveal the transformation between SO4 . - and S2 O8 2- Optimize the parameters to improve the accumulation of PS by full factor design. PS was activated by heat and quinones to produce SO4 . - The possible degradation pathway of TCH was proposed.